2021
DOI: 10.35536/ljb.2021.v9.i2.a4
|View full text |Cite
|
Sign up to set email alerts
|

(In) Direct Effects of Customer-Defined Market Orientation on Brand Loyalty through Purchase Intention and Brand Image: A Parallel Mediation Approach

Abstract: This study investigates the impact of market orientation on brand loyalty, primarily through variables pertaining to the purchase intention and brand image. In order to achieve this aim, this study have resorted to testing the relationships between customer-defined market orientation and purchase intention, and the brand image, leading to brand loyalty. In this regard, the study is quantitative in nature, and uses the cross-sectional design. For this purpose, the primary data were collected from gold jewelry c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…These evaluations have significantly predicted consumer orientation, equal distribution of income, and the effective use of resources in different areas of society. Other research in the field (Anwar et al, 2019; Eklof et al, 2020; Khan & Ghouri, 2018; Khan, Ul Abedin et al, 2021) found that a positive BI is linked to a high level of CS, which increases customer loyalty and protects market share.…”
Section: Literature Reviewmentioning
confidence: 93%
“…These evaluations have significantly predicted consumer orientation, equal distribution of income, and the effective use of resources in different areas of society. Other research in the field (Anwar et al, 2019; Eklof et al, 2020; Khan & Ghouri, 2018; Khan, Ul Abedin et al, 2021) found that a positive BI is linked to a high level of CS, which increases customer loyalty and protects market share.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Tariff exemption for importing specialized machinery and materials that are unavailable locally allows them to improve their production efficiency and quality (Khan et al, 2021). This exemption also provides access to diversified raw materials that widen the scope of their production.…”
Section: Tax Benefitsmentioning
confidence: 99%